Identification of Aedes (Diptera: Culicidae) Species and Arboviruses Circulating in Arauca, Eastern Colombia - Martínez, David; Hernández, Carolina; Muñoz, Marina; Armesto, Yulieth; Cuervo, Andres; Ramírez, Juan David (Frontiers in Ecology and Evolution, 2020)
The identification of vector species and their natural infection with arboviruses results in important data for the control of transmission. However, for the eastern region of Colombia, this information is limited. Therefore, this study morphologically and molecularly identified species of the genus Aedes and the detection of arboviruses (Dengue, Chikungunya, Zika and Mayaro) in female mosquitoes (individually) present in three municipalities (Saravena, Arauquita and Tame) by amplifying the genetic material using RT-PCR (reverse transcriptase polymerase chain reaction) in the department of Arauca, eastern Colombia. Inconsistencies between morphological and molecular identification were detected in 13 individuals with Ae. albopictus initially determined as Ae. aegypti based on morphology (n = 13). Molecular identification showed the simultaneous presence of Ae. aegypti (n = 111) and Ae. albopictus (n = 58) in the urban municipalities of Saravena and Arauquita. These individuals were naturally infected with Dengue virus type 1 (DENV-1) and Chikungunya virus (CHIKV). The most frequent arbovirus was DENV-1 with an infection rate of 24.3% (11/27) for Ae. aegypti and 39.7% (23/58) for Ae. Albopictus, which was followed by CHIKV with an infection rate of 1.8% for Ae. aegypti (2/111) and 6.9% for Ae. albopictus (4/58). Additionally, a mixed infection of DENV-1 and CHIKV was obtained in 4.5% of Ae. aegypti (5/111). Zika virus (ZIKV) and Mayaro virus (MAYV) infections were not detected. This study found that barcoding (fragment gene COI) is a successful method for identifying Aedes species. Additionally, we recommend the individual processing of insects as a more accurate strategy for arboviruses detection since the infection rate is obtained and co-infection between DENV-1 and CHIKV is also possible.